Comparative analysis of alpha-fetoprotein, carbohydrate antigen 19-9, carcinoembryonic antigen, and prostate-specific antigen among conventional cigarette smokers, heated tobacco product users and quitters - Dae-Hyun Kim; Seung-Wan Hong; Naeun Park (Tobacco Induced Diseases)
Introduction The association of Heated Tobacco Products (HTPs) use on cancerrelated biomarkers remains unclear. This study aimed to compare the levels of tumor markers, specifically alpha-fetoprotein (AFP), carbohydrate antigen 19-9 (CA 19-9), carcinoembryonic antigen (CEA), and prostate-specific antigen (PSA), between combustible cigarette (CC) smokers, any HTP users, and quitters.